1989
DOI: 10.1177/019262338901700208
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Gland: Chemically Induced Structural and Functional Changes in the Cortex

Abstract: The adrenal cortex is the target of a surprisingly large number of exogenous chemicals. Until recently, the toxic action of these chemicals was discovered serendipitously. Following our observations that acrylonitrile, cystearnine or pyrazole induces hemorrhagic adrenocortical necrosis in the rat, we recently recognized a structure-activity correlation which predicts the adrenocorticolytic property of alkyl chemicals, i.e., 2-3-carbons with double or triple bonds and with nucleophilic terminal radicals (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 25 publications
(6 reference statements)
0
11
1
Order By: Relevance
“…The coagulative necrosis found in this study differed from the lesions found in adrenal glands exposed to chemical exogenous substances (43), septicemia or high levels of adrenocorticotrophic hormone (33), because the necrosis was at the specific location of the corticomedullary junction and the inflammatory infiltrate was discrete and composed mainly of macrophages without associated hemorrhage.…”
Section: Discussioncontrasting
confidence: 79%
“…The coagulative necrosis found in this study differed from the lesions found in adrenal glands exposed to chemical exogenous substances (43), septicemia or high levels of adrenocorticotrophic hormone (33), because the necrosis was at the specific location of the corticomedullary junction and the inflammatory infiltrate was discrete and composed mainly of macrophages without associated hemorrhage.…”
Section: Discussioncontrasting
confidence: 79%
“…Ribelin, 1984;Szabo and Lippe, 1989;Colby and Longhurst, 1992;Colby, 1996;Rosol et al, 2001) and medulla (e.g. Tucker, 1996;Rosol et al, 2001) largely derived from results of in vivo studies and descriptive histopathological lesions, with the cortex being the most frequently affected site.…”
Section: Chemicals Known To Cause Adrenal Toxicitymentioning
confidence: 99%
“…Ribelin, 1984;Szabo and Lippe, 1989;Colby and Longhurst, 1992;Colby, 1996;Raven and Hinson, 1996;Hinson and Raven, 1999;Rosol et al, 2001) and to the adrenal medulla (Tucker, 1996;Hinson and Raven, 1999;Rosol et al, 2001) but the potential molecular basis of such effects has only more recently emerged and this, and toxicologically relevant endocrinology, is discussed later. Identified factors predisposing the adrenal to toxic insult in vivo include: the large number of potential toxicological targets such as receptors, enzymes and peripheral hormone carrier molecules; high vascularity and disproportionately large blood volume received per unit mass; the high content of unsaturated fatty acids in adrenocortical cell membranes susceptible to lipid peroxidation; lipophilicity due to rich cholesterol and steroid content; and the high content of cytochrome P450 (CYP) enzymes present in the adrenal cortex, that normally catalyse steroidogenesis, but which can also produce reactive metabolites of toxicants and hydroxylation reactions that may generate free radicals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among the endocrine tissues, the adrenal cortex appears to be one of the most vulnerable to chemically induced injury and in fact develops neoplastic or non-neoplastic lesions in response to a wide variety of chemicals (4,10,24). 4-Hydroxyaminoquinoline 1-oxide (4HAQO), an intermediate metabolite and possible proximate carcinogenic form of 4-nitroquinoline 1-oxide (12), is both toxic and carcinogenic to organs such as the pancreas and lung in rodents (9,20).…”
Section: Introductionmentioning
confidence: 99%